Study on the Effect of Replacing Traditional Feed by Partial Concentrate Ration on Growth Performance of Growing Crossbred Piglets in Rural Tribal Areas of Manipur - Singh, N. Muhindro; Singh, M. Dhaneswar; Savino, N.; Thokchom, D.S. (Indian Journal of Extension Education, 2018)
The present investigation was designed to study the effect of concentrate ration supplemented to traditional pig feed on the growth rate of crossbred piglets. Studies were carried out on twelve weaned crossbred piglets aged about 3 months of age at the Department of Animal Science, Central Agricultural University, Imphal, Manipur. The piglets were grouped into two treatment groups i.e. T1 and T2 having 6 piglets in each group on the basis of body weight in such a way that mean body weight of each group remained almost same. The control diet (T1) was prepared with common traditional feed which are traditionally fed to pigs in the rural tribal areas of Senapati district, Manipur. The experimental diet (T2) was constituted by replacing 25% of T1 diet with concentrate feed. The live weight at day 1 of the experiment were 13.83 + 0.40 and 13.75 + 0.44 Kg in T1 and T2 dietary groups, respectively which did not differ significantly from each other. However, at the end of experimental period of 16th week, significantly higher body weight was noticed in T2 (43.08 + 1.81 Kg) than those of T1 (35.66 + 1.24 Kg). Similarly, significantly higher average daily, weekly and total weight gain during experimental period of 16th weeks was observed in the pigs maintained on T2 diet than those of T1 group, the value being 194.94 + 9.05 and 261.90 + 13.52 gm, 1.36 + 0.06 and 1.83 + 0.09 Kg and 21.83 + 0.01 and 29.33 + 1.51 Kg in T1 and T2 diets, respectively. It was concluded that supplementation of the traditional feed by at least 25% concentrate ration induces faster growth, lower mortality and better reproductive performance of crossbred piglets.
Keywords: Average daily weight gain; growth performance; traditional pig feed